PORE SIZE DISTRIBUTION AND FLOW CHARACTERISTICS IN A FORESTED HEADWATER CATCHMENT - Kasdi Subagyono; Tadashi Tanaka (Indonesian Institute of Sciences, 2009)
ABSTRACT It is obvious in recent publications that pores and pores size distribution play an important role in flow generation, yet the study of dynamic behavior of the effects of pores and pores size distribution on flow characteristics is somewhat rare. As micro pores, mezzo pores and macro pores are various in the soil, the distribution as well as characteristics of those pores are the major factor of flow characteristics in the soils. Pores size distribution was determined considering the volumetric water content at each matric head defined from soil water characteristics curves. Mathematically, pores size distribution is calculated using formula of r = 0.15/h, where r is radius of the pore and h is matric head. The flux of water was determined by installing tensiometer and piezometer in a transect across the hillslope and riparian zone. The results showed that the different of those between hillslope and riparian provides insight that the effects of pores and pores size distribution varies with hydrological zone. In riparian zone, flows are highly affected by micropores (R2 = 0.49), mezopores (R2 = 0.26) and total porosity (R2 = 0.28), while in hillslope side only micropore is dominant. The relationship between pores size distribution and water flow suggested that in hillslope side the flow was dominated by slow flow as micro pores has affected, while in riparian zone the rapid flow was more obvious as mezopores and total porosity have affected.